Effects of Different Green Teas on Obesity and Non-Alcoholic Fatty Liver Disease Induced by a High-Fat Diet in Mice - Zhou, Dan-Dan; Mao, Qian-Qian; Li, Bang-Yan; Saimaiti, Adila; Huang, Si-Yu; Xiong, Ruo-Gu; Shang, Ao; Luo, Min; Li, Hang-Yu; Gan, Ren-You; Li, Hua-Bin; Li, Sha (Frontiers in Nutrition, 2022)
Nonalcoholic fatty liver disease (NAFLD) and obesity are serious public health problems. Green tea is widely consumed in the world, and different green teas could possess different bioactivities. In this study, effects of 10 selected green teas on obesity and NAFLD were evaluated and compared. The mice fed with high-fat diet were intervened with green tea extract (200 mg/kg body weight) for 15 weeks. Most of these teas were firstly evaluated for their effects on obesity and NAFLD. The results showed that Selenium-Enriched Chaoqing Green Tea and Jieyang Chaoqing Tea showed the most prominent inhibition on body weight gain. In addition, Jieyang Chaoqing Tea, Taiping Houkui Tea, and Selenium-Enriched Chaoqing Green Tea exerted the most notable effect on NAFLD, which was attributed to decreasing body weight as well as lipid content and ameliorating oxidative stress. Furthermore, 13 phytochemicals were determined in these teas by high-performance liquid chromatography, and the correlation analysis found that epigallocatechin gallate, gallocatechin and epigallocatechin might contribute to the decrease of hepatic weight, while epicatechin might reduce oxidative stress. In general, several green teas could prevent the development of obesity and NAFLD, and could be developed into functional foods. This study was also helpful for the public to select appropriate tea to prevent obesity and NAFLD.